Pengaruh Persepsi dan Trend terhadap Keputusan Pembelian Vape dan HTP (Heated Tobacco Product) pada Konsumen Gen-Z - Feby Saputro, Danang; Harjanti, Agustina Eka; Darsin, Darsin (STMIK Amika Soppeng, 2025)
The development of modern lifestyles and the high use of social media encourage Generation Z to increase the consumption of vape and heated tobacco products (HTP), which are often considered symbols of urban lifestyle. This study aims to determine the influence of perceptions and trends on vape and HTP purchasing decisions among Gen-Z consumers in Jepara Regency. This study uses a quantitative descriptive approach through an online questionnaire-based survey method to 100 respondents aged 18–27 who have purchased or used vape or HTP. Data were analyzed using PLS-SEM with the help of SmartPLS. The results showed that the R² value was 0.219, meaning that 21.9% of the variation in purchasing decisions was explained by perceptions and trends, while the rest was influenced by other factors outside the research model. The perception variable was proven to have a positive and significant effect on purchasing decisions with a path coefficient of 0.461, a t-statistic of 5.592, and a p-value of 0.000, while the trend variable had no significant effect as seen from the path coefficient of 0.018, a t-statistic of 0.109, and a p-value of 0.914. Perceptions of product quality and benefits are the most dominant factors driving purchasing decisions, while social media trends have no impact because consumers' perceptions are already pre-formed. Manufacturers recommend focusing marketing strategies on building positive perceptions through product education, quality enhancement, and emphasizing utility, although trends can still be leveraged to attract new consumers.